Fundamentalisme dan Radikalisme dalam Islam: Analisis terhadap Gerakan dan Efeknya terhadap Perkembangan Islam - Hamzah Saputra; Darussalam Syamsudin (Jurnal Pelita Nusantara, 2025)
Islamic da'wah is essentially a process of communicating divine values aimed at guiding humanity toward goodness, peace, and the common good. However, in the contemporary Indonesian context, da'wah faces serious challenges due to the strengthening of Islamic fundamentalism and radicalism, which often present religion in an exclusive, textual, and confrontational manner. This article aims to analyze Islamic fundamentalism and radicalism as problems in da'wah and religious communication and to formulate a preventative da'wah model relevant to Indonesia's social reality. This research uses a qualitative approach with a case study method, through in-depth interviews, participant observation, and document analysis, enriched by a review of literature related to digital da'wah and religious moderation. The results show that radicalism develops not only due to narrow religious understanding but also due to dysfunctional da'wah communication that fails to build dialogue, empathy, and awareness of plurality, especially in the digital space. The spread of exclusive religious narratives through social media increases the vulnerability of the younger generation to extreme ideologies. Therefore, this study emphasizes the urgency of preventive preaching as a transformational communication model through strengthening religious and digital literacy, cultural communication, institutional synergy, and building community resilience to strengthen religious moderation and social cohesion in Indonesia.